Cytotoxic and antimicrobial activities of alkaloids from tabernaemontana corymbosa - Bakhtiar, M. Taher; Nur ‘Izzati, Mansor; Darnis, Deny Susanti (2011)
The investigations were made based on the fact that alkaloids from Apocynaceae family are potential for medicinal purposes. The aim of the study was to explore the potential cytotoxic and antimicrobial activities of alkaloids extracted from T. corymbosa and to provide scientific basis for further studies of T. corymbosa. The alkaloids were extracted from stembarks of Tabernaemontana corymbosa using maceration and acid-base extraction methods. Then, the extracts were tested for their cytotoxic and antimicrobial activities. The cytotoxic activity was studied in vitro using human non-small lung carcinoma (A549) and human cervical carcinoma (C33A). The cells were exposed to three crude alkaloid extracts of T. corymbosa. The cytotoxic effects of these crude alkaloid extracts were evaluated by MTT assay. In antimicrobial activity study, the crude alkaloid extracts of T. corymbosa were tested against four bacterial and two fungi species by using disc diffusion method. Bacillus cereus ATCC11778, Pseudomonas aeruginosa ATCC27853, Staphylococcus aureus ATCC25923, Escherichia coli ATCC35218, Cryptococcus neoformans ATCC90112 and Candida albicans ATCC10231 were used in the study. Cytotoxicity study showed that only crude B alkaloids exhibited cytotoxic effect against A549 and C33A cancer cells, giving an IC50 as low as 7.81 μg/mL and 3.91 μg/mL, respectively. In antimicrobial activity, the zones of inhibition against the tested bacteria were found in the range of 7.00 to 14.75 mm, along with their MIC and MBC/MFC values ranging from 0.37-1.11 mg/mL and 3.33-10.00 mg/mL, respectively. Those results suggest that T. corymbosa contains alkaloids that active as cytotoxic and antimicrobial agents.